Eficácia do ceftiofur no tratamento estendido intramamário da mastite subclínica por estafilococos em primíparas bovinas - Motta, Rodrigo Garcia [UNESP] (2015)
This study investigated the efficacy of extended ceftiofur intramammary therapy using 10 applications by five days in primiparous heifers infected by staphylococcal subclinical mastitis. Sixty Holstein cows were divided in four groups: G1 = negative group or without staphylococcal infection, CMT-negative and SCC<200.000 cells/mL; G2 = untreated group with staphylococcal infection, CMT-positive and SCC>200.000 cells/mL; G3 = treated early lactation group (15-100 days of lactation) with staphylococcal infection, CMT-positive and SCC>200.000 cells/mL, G4 = treated late of lactation group (101-200 days of lactation) with staphylococcal infection, CMT-positive and SCC>200.000 cells/mL. The milk samples were collected at five moments: M0 or day zero (diagnosis of subclinical mastitis), M1 = 7 days after diagnosis of subclinical mastitis and early extended therapy, M2 = 2 days after the end of the extended treatment (day 14 after the diagnosis of subclinical mastitis), M3 = 21 days after diagnosis of mastitis (9 days after the end of treatment), M4 = 28 days after diagnosis of mastitis (16 days after the end of treatment). In the groups treated with intramammary ceftiofur, microbiological cure was observed with reduction in SCC in 73.34% and 46.66% of animals for G3 and G4, respectively. Thus, in the treated (G3 + G4) and untreated (G2) groups, microbiological cure rates were 60.00% and 26.66% (p<0.05), respectively. Forty-five Staphylococcus spp. strains were isolated. From these, S. aureus (51.12%), S. intermedius (40.0%), and S. epidermidis (8.88%) were the most common species. In vitro antimicrobial susceptibility profile of isolates showed that the most effective drugs were oxacillin (80.0%), ceftiofur (77.78%), and cephalexin (77.78%), followed by ceftriaxone (69.0%), ciprofloxacin (66.66%) and gentamicin (60,0%). In contrast, high-resistance rates of isolates were founded to cloxacillin (24.44%), penicillin...